Case Study of Stress Corrosion Cracking (SCC) on Natural Gas Pipeline and Types of Repairs (The International Journal of Engineering & Information Technology (IJEIT), 2025)
Oil and gas pipelines are prone to various deficiencies, including stress corrosion cracking (SCC). This case study explores the methods and best practices for repairing a 34-inch distribution network of gas transmission and supply pipelines that serve various consumers along the Libyan coastline. It also highlights the vital importance of this facility in powering key industries, such as power plants, steel mills, and cement factories. The focus is on preventing and addressing SCC, including the use of split sleeving, repair clamps, and non-destructive testing (NDT) techniques.